Disulfide-crosslinked albumin hydrogels. Issue 16 (12th April 2016) - Sun, Yuling; Huang, Yanbin
Abstract : Albumin hydrogels crosslinked by disulfide bonds between the protein's own thiol groups. Abstract : With its clinically-demonstrated safety profile and huge potential for functionalization, albumin should be an ideal biomaterial. In this study, we obtained disulfide-crosslinked albumin hydrogels using the protein's own thiol groups. In the water solutions with denaturants such as urea and guanidinium, the disulfide-crosslinked albumin hydrogels showed a normal swelling profile. However, in water solutions without denaturants, the same hydrogels showed erosion behavior similar to the physical gels. We explained these rich swelling behaviors by proposing that an inter-to-intramolecular disulfide exchange occurred in the eroding hydrogel. The albumin hydrogels are injectable through narrow needles and a doxorubicin-releasing study was used to demonstrate their potential applications.